Cobalamin (vitamin B12) biosynthesis in Rhodobacter capsulatus. (August 2002) - McGoldrick, H.; Deery, E.; Warren, M.; Heathcote, P.
Abstract : In Rhodobacter capsulatus, cobalamin biosynthesis has been shown to occur when the bacteria are grown either aerobically or anaerobically. However, a comparison of the main cobalamin biosynthetic operon found within R. capsulatus would suggest that the encoded proteins belong to the oxygen-dependent pathway for cobalamin biosynthesis, although, significantly, no homologue of the essential mono-oxygenase CobG has yet been detected. Nonetheless, within this main cob operon is found a large open reading frame termed orf663 that is not found in any other cobalamin biosynthetic operon. When overproduced in Escherichia coli, orf663 was found to encode a 90 kDa integral membrane protein. Some of this protein is cleaved within E. coli to give a soluble N-terminal region that can easily be purified and yields a 50 kDa flavoprotein. When expressed in harness with the genes for precorrin-3a synthesis, ORF663 appears to mediate the transformation of precorrin-3a into a new chromophoric compound. Another open reading frame in close proximity to orf663 is termed orf647, and was found to encode a 2Fe-2S ferredoxin-like protein. We suggest that these two proteins may provide an alternative oxygen-independent mechanism for ring contraction within R. capsulatus .